Tinjauan Yuridis Mengenai Pengawasan Terhadap Pedoman Perilaku Penyiaran Platform Media Sosial Di Indonesia - Elwindhi Febrian (Universitas Islam Indonesia, 2020)
The purpose of this study is to examine and analyze the supervision of code of conduct in broadcasting on social media platform based on the laws and regulations in Indonesia and to identify the law that regulates broadcasting on social media platforms considering both broadcasting and platform are regulated under different laws. The results of the study conclude that supervision of code of conduct in broadcasting on social media platform is carried out by the Ministry of Communication and Information with reference to the prohibitions regulated in Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law). Broadcasting on social media platform has different characteristics from the definition of broadcasting stipulated in the Broadcasting Law. Based on the origin of lex specialis, ITE Law is more dominant in regulating broadcasting on social media platform hence the broadcasting code of conduct and the implementation of sanctions are still subject to the provisions stipulated in the ITE Law and its derivative regulations.